Christian compassion and solidarity within capitalist contexts - Dagmang, Ferdinand D. (2006)
The theories and practices of capitalism in different places and periods also produced various theories and practices of welfare which have implications for the understanding and practice of solidarity as well as that of capitalism itself. This article sets the possible expressions of Christian compassion and solidarity against the backdrop of capitalist work, commodity circulation and the practice of welfare. It offers a stage towards a more integrated reflection on the possibility and limits of social assistance and solidarity; something necessary for the evaluation of everyday practical moral reasoning or proposals of some forms of social ethics.
Keywords: Capitalism -- Religious aspects; Capitalism -- Social aspects; Commodity chains; Christian ethics